2019
DOI: 10.1002/ecs2.2849
|View full text |Cite
|
Sign up to set email alerts
|

Time since fire strongly and variously influences anthophilous insects in a fire‐prone landscape

Abstract: Drivers of species productivity and ecosystem function are of great ecological significance. In fire‐prone ecosystems, dispersion patterns of important pollinator species are driven by the various fire events over space and time. However, different species have varying responses to fire intensity and frequency. Here, we assess how time since last fire influences abundance, composition, and dispersion patterns of flowering plants and anthophiles in a highly fire‐prone landscape. We classified study area into ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Similar to previous studies of fire ecology and invertebrates (e.g. Adedoja et al., 2019), the interpretation of our findings may be limited given the potential influence of other environmental factors. For example, the sites of different fire ages were not randomly distributed throughout the landscape and surrounding land use, soil types and microclimate were not controlled for.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to previous studies of fire ecology and invertebrates (e.g. Adedoja et al., 2019), the interpretation of our findings may be limited given the potential influence of other environmental factors. For example, the sites of different fire ages were not randomly distributed throughout the landscape and surrounding land use, soil types and microclimate were not controlled for.…”
Section: Discussionsupporting
confidence: 88%
“…For optimal plant regeneration and removal of dominant shrub, it is recommended that renosterveld patches are burned approximately every 10–15 years (Esler et al., 2014; Kraaij & van Wilgen, 2014). Limited understanding of insect ecology in renosterveld (Topp & Loos, 2019a) makes it difficult to assess how fire regimes may impact insect diversity in the fynbos biome (Procheş & Cowling, 2006), although it has been shown that bees may benefit from flower abundance resulting from regular burns in the CFR (Adedoja et al., 2019) and ecologically appropriate fire management is key to support diverse butterfly populations elsewhere in South Africa (Gaigher et al., 2019). Given the importance of understanding management impacts and ecological processes in renosterveld (Topp & Loos, 2019a) and the inclusion of habitat and landscape conservation as key strategies for butterfly conservation in South Africa (Edge & Mecenero, 2015), our intention was therefore to investigate the relationship between fire in renosterveld and butterfly diversity in the CFR.…”
Section: Introductionmentioning
confidence: 99%
“…This exposes the industry to a substantial risk in a system where the bee keeping is already under stress (Pirk et al., 2014). Habitat loss caused by climate change, the increasing frequency of fires and eucalyptus removal reduces important foraging resources for wild and managed bees throughout the year (Adedoja et al., 2019; De Lange et al., 2013), and pathogens and diseases are known stressors for bee keepers (Allsopp, 2004). Increasing managed pollinator efficiency through the augmentation of in‐farm floral resources could reduce the number of hives required per unit area of orchard.…”
Section: Discussionmentioning
confidence: 99%
“…Flowering plant composition showed a significant association with the composition of insect pollinators in both savanna and rain forest vegetation zones. This underscores the key role that flowering plants play in driving insect pollinator diversity in the tropics (Adedoja & Kehinde, 2018; Stein et al, 2018), as well as in other areas (Adedoja et al, 2019; Geslina et al, 2016). While flowering plant species richness and abundance is well known to influence pollinator diversity (Adedoja et al, 2019; Stein et al, 2018), we show here that the species composition of flowering plants is critical for the distribution of insect pollinators in both PAs and unprotected areas.…”
Section: Discussionmentioning
confidence: 80%
“…This underscores the key role that flowering plants play in driving insect pollinator diversity in the tropics (Adedoja & Kehinde, 2018; Stein et al, 2018), as well as in other areas (Adedoja et al, 2019; Geslina et al, 2016). While flowering plant species richness and abundance is well known to influence pollinator diversity (Adedoja et al, 2019; Stein et al, 2018), we show here that the species composition of flowering plants is critical for the distribution of insect pollinators in both PAs and unprotected areas. Some species‐specific requirements of different pollinators may influence their distribution across ecosystems with various traits of flowering plants.…”
Section: Discussionmentioning
confidence: 80%